2015
DOI: 10.4103/1947-2714.166220
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and etiological patterns of gastric outlet obstruction in Kerala, South India

Abstract: Background:In the modern era, the major cause of gastric outlet obstruction (GOO) is known to be a malignancy, especially in the developed world. Many books and articles do suggest that the benign causes continue to be the major cause of GOO in the developing world however, there is growing evidence proving the contrary. Males were (more commonly) affected females and individuals in their fifth and sixth decade have been the predominant age group in the majority of studies. There is a minimal data of GOO from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…In this study, gallbladder carcinoma was the most common cause of malignant GOO. Etiology of malignant GOO in this study is in accordance with the other Indian studies, [22][23][24][25] although quite different from other parts of the world where pancreatic and gastric cancers are more common. 11,26,27 A longstanding gall stone is associated with higher incidence of gall bladder carcinoma, particularly in women living in the Gangetic plains of northern India.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, gallbladder carcinoma was the most common cause of malignant GOO. Etiology of malignant GOO in this study is in accordance with the other Indian studies, [22][23][24][25] although quite different from other parts of the world where pancreatic and gastric cancers are more common. 11,26,27 A longstanding gall stone is associated with higher incidence of gall bladder carcinoma, particularly in women living in the Gangetic plains of northern India.…”
Section: Discussionsupporting
confidence: 91%
“…In our study Group A (Laparoscopic hand sewn anastomosis) comprised of 20 patients between the ages of 50 and 70 years (mean age: 59.6±6.29 years) while Group B (Laparoscopic stapled anastomosis) comprised of 20 patients in age range of 50 to 70 years (mean age: 60.9±6.77 years).Most of the patients were in age range of 50-59 years of age in both groups. Study done by Vivek, et al [12] showed the majority of the study population was between the age group of 40 and 80 years with a maximum number of individuals falling in the group of 51-60 years In study by Linda P. Zhang, et al [13] in a study a total of 28 patients were reviewed. Average age was 68 (range, 25 to 99).…”
Section: Discussionmentioning
confidence: 99%
“…The last several decades have seen a trend toward more cases due to cancer and fewer due to benign causes. [3][4][5][6][7][8][9][10][11][12][13][14] In earlier studies in both developed and developing countries, gastric adenocarcinoma was the most common malignant cause of gastric outlet obstruction. Since then, it has become less common in Western countries, although it remains more common in Asia and Africa.…”
Section: Less Gastric Cancer More Pancreatic Cancermentioning
confidence: 99%
“…Since then, it has become less common in Western countries, although it remains more common in Asia and Africa. [7][8][9][10][11][12][13][14] This trend likely refl ects environmental factors, including decreased prevalence of Helicobacter pylori infection, a major risk factor for gastric cancer, in Western countries. [15][16][17] At the same time, pancreatic cancer is on the rise, 16 and up to 20% of patients with pancreatic cancer develop gastric outlet obstruction.…”
Section: Less Gastric Cancer More Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation